PROBLEMS OF FORMATION OF THE NATIONAL MENTALITY OF YOUTH IN THE WISDOM OF THE PEOPLE (ResearchJet Journal of Analysis and Inventions, 2021)
This article emphasizes the role and importance of examples of folk wisdom, oral literature, and fiction heritage in the formation of the national mentality of young people. In particular, new tasks have been set in the study of history and national values of the Karakalpak people. The article presents the great views on ancient national customs and traditions, ethnic history and ethnogenesis of the Karakalpak people.